EGCG and DOX dual-drug-loaded enzyme-responsive nanovesicles boost mitochondrial-mediated ICD for improved immunotherapy - Zhou, Mengxue; Wang, Ying; Cui, Hongchun; Geng, Huan; Ruan, Lifo; Zhao, Yanni; Zhou, Chuang; Dai, Weidong; Chen, Jun; Yu, Jizhong; Lv, Haipeng; Lin, Zhi (Frontiers in Pharmacology, 2025)
Enhancing cancer immunotherapy using methods that induce immunogenic cell death (ICD) can significantly improve its effectiveness and profoundly influence its role as a highly efficient cancer treatment strategy. However, the limited penetration of cytotoxic T cells into tumors, owing to dense tumor fibrosis, remains a significant barrier to immunotherapy. A tumor microenvironment-sensitive intelligent dual-drug delivery system was developed to simultaneously deliver epigallocatechin-3-gallate (EGCG) and doxorubicin (DOX) to mitochondria. EGCG enhanced the mitochondria-targeted action of DOX and increased damage to the mitochondrial electron transport chain which facilitated capturing electrons in the mitochondrial matrix of DOX. Subsequently, DOX molecules form a semiquinone intermediate and electrons are transferred to oxygen to generate reactive oxygen species (ROS) that induce mitochondrial apoptosis. These results indicate that EGCG amplifies the combined effects of chemo/chemodynamic therapy of DOX, demonstrating a pronounced synergistic ICD effect that recruits CD8+ T cells to the tumor microenvironment (TME). In addition, EGCG promotes T-cell infiltration into tumor tissues by inhibiting the transforming growth factor-β signaling pathway, thereby significantly enhancing antitumor efficacy. This study advances the efficacy of immunotherapy through bidirectional synergy, which not only enhances intrinsic tumor immunogenicity but also overcomes the extrinsic physical barriers of tumors, providing a new direction for the development of broadly applicable immunotherapies.